Open-fault diagnosis and tolerant control of a dual inverter fed open-end winding interior permanent magnet synchronous motor - Lee, Hyung Woo; Lee, Kyo Beum (Journal of Power Electronics, 2024)
This paper proposes a diagnostic and fault-tolerant method for an open-fault condition in dual inverters with open-end winding interior permanent magnet synchronous motors (OEW-IPMSMs). Certain switch pairs show similar behavior in the output current in an open-fault condition due to the structural characteristics of the two-level dual inverter. This work presents a method for detecting open-fault conditions and ensuring a fault-tolerant operation. The proposed method is applied in dual inverters with isolated voltage sources for driving OEW-IPMSM. In the event of an open-fault condition, a pair of switches containing the faulty switch is identified based on the stator current. Subsequently, the switch with the open-fault condition is determined, and fault-tolerant control for a faulty switch is immediately performed through a single-mode operation using zero-voltage vectors. The effectiveness of the proposed detection and tolerant control method is confirmed through simulation and experimental results.
Keywords: Dual inverters; End winding IPMSM, two; End windings; Fault; Fault conditions; Fault, open; Level dual inverte; Open faults; Open-end windings; Tolerant control, open; End winding IPMSM, Two; Fault; Fault, Open; Level dual inverter; Tolerant control, Open